The demand incidence of symptomatic ankle osteoarthritis presenting to foot and ankle surgeons in the United Kingdom. - Goldberg, A; MacGregor, A; Dawson, J; Singh, D; Cullen, N; Sharp, R; Cooke, P (2012)
BACKGROUND: Ankle arthritis is a cause of major disability; however reports in the literature on the incidence of ankle osteoarthritis are rare. OBJECTIVES: To explore the methodological challenges in obtaining an incidence of ankle osteoarthritis and to estimate the incidence of symptomatic osteoarthritis presenting to Foot and Ankle specialists in the UK. METHODS: We searched available national diagnosis databases and also sent out a questionnaire-based survey to all Consultant members of the British Orthopaedic Foot and Ankle Society (n=180). RESULTS: 123 completed survey questionnaires were returned (68%) with each surgeon seeing on average 160 cases of symptomatic ankle arthritis and performing on average 20 definitive procedures for end-stage ankle osteoarthritis per year. There are no internationally agreed diagnostic or treatment codes specific for ankle osteoarthritis. CONCLUSION: There are an estimated 29,000 cases of symptomatic ankle osteoarthritis being referred to specialists in the UK, representing a demand incidence of 47.7 per 100,000. 3000 definitive operations to treat end stage ankle osteoarthritis take place in the UK annually. We recommend that specific codes pertaining to ankle arthritis and its treatment be included in any future revisions of the WHO International Classification of Diseases (ICD) and operative procedure coding systems.